First stable isotope and mercury assessment of bonnethead and Caribbean sharpnose sharks from a potential nursery ground in the Archipelago of Bocas del Toro, Panamanian Caribbean - Barragán-Barrera, Dalia C.; Polo-Silva, Carlos J.; González, Cindy; Rodríguez, Miguel; Baldrich, Laura; Bermúdez-Rivas, Christian; Moncaleano-Niño, Ángela Margarita; Bustamante, Paco; Caballero, Susana; Luna-Acosta, Andrea (Frontiers in Marine Science, 2024)
Bonnethead and Caribbean sharpnose sharks have coastal habits, making them susceptible to overexploitation like the bonnethead shark, which is listed as endangered by the IUCN. Marine Protected Areas (MPAs) have been proposed as a management measure to control shark-exploitation. Furthermore, it's essential to identify key-areas where nursery grounds (NG) and adult habitats overlap to prioritize conservation zones within MPAs. Along the Caribbean Sea, several NG have been identified for larger shark species, but little is known for smaller sharks. In Bocas_del_Toro (BDT-Panamanian_Caribbean), both bonnethead and Caribbean sharpnose sharks are distributed, and the first one appears to be genetically isolated. BDT has a local MPA, where a NG identified near Solarte Island, is not included. With the goal of furnishing ecological information on bonnethead (N=6) and Caribbean sharpnose (N=15) sharks within this potential NG, we assessed stable isotopes (δ 13 C and δ 15 N) and total-mercury (THg) values in their fins. Our findings showed more small adults in the NG, which highlights the need of conduct an exhaustive study to further characterize this area. Moreover, our results suggest no niche-partitioning between the two species, whose diet primarily consist of small prey-items, which is reflected by the significant and negative relationship between isotopic values. Consequently, both species exhibited low THg levels in their fins. Based on these initial findings and previous genetic data, it appears that BDT serves a crucial habitat for sharks. Thus, ensuring their conservation could be effectively achieved by extending the local MPA to encompass the potential NG.